A supervisory loop approach to fulfill workspace constraints in redundant robots - Gracia, Luis (2012)
An approach based on geometric invariance and sliding mode ideas is proposed for redundancy resolution in robotic systems to fulfill configuration and workspace constraints caused by robot mechanical limits, collision avoidance, industrial security, etc. Some interesting features of the proposal are that: (1) it can be interpreted as a limit case of the classical potential field-based approach for collision avoidance which requires using variable structure control concepts, (2) it allows reaching the limit surface of the constraints smoothly, depending on a free design parameter, and (3) it can be easily added as a supervisory block to pre-existing redundancy resolution schemes. The algorithm is evaluated in simulation on a 6R planar robot and on the freely accessible 6R robot model PUMA-560, for which the main features of the method are illustrated. © 2011 Elsevier B.V. All rights reserved.